Student Response to Teachers in the Implementation of Pancasila Student Profile Strengthening Project - Alinie Dewi Ariyani Sriyono; Rusijono Rusijono; Karwanto Karwanto (research, training and philanthropy institution Natural Aceh, 2023)
The Pancasila student profile is a character development in the independent curriculum that students must develop optimally. Professional teachers are central to developing students' character in the Pancasila student profile. Student responses to teachers are needed to determine if a teacher already has professional competence to support students in developing their character in the P5 program. This study examined students' responses to teachers in implementing the project to strengthen the Pancasila student profile (P5). The approach used is descriptive qualitative. Using this approach, the researcher can emphasize the importance of students' responses to the teacher, and the researcher can gain a clear and in-depth understanding of the actual condition of the teacher. Data was taken using questionnaires, interviews, and observations. The results of the analysis of this study were that the responses from students indicated that several teachers could not make the class atmosphere lively when giving material in the P5 program, so learning became boring and monotonous. The implications of this research for the teacher concerned, the school will take the following actions: a. training through the Merdeka Teaching Training application provided by the Ministry of Education and Culture, b. Join the teacher community to be able to share best practices in learning. c. through the school's MGMP.